Convective Coefficient and Evaporative in Forced Flow Solar Still - Oktavian, Akbar; Mugisidi, Dan; Alamsyach, Rizky; Heriyani, Oktarina (Jurnal Asiimetrik: Jurnal Ilmiah Rekayasa & Inovasi, 2024)
The water crisis is a significant global problem, with more than 2 billion people lacking water and 1.1 billion having no access to clean water. Desalination, a method of converting seawater into fresh water by removing salt, is a potential solution to help coastal populations. This study aims to determine the convection and evaporation heat transfer coefficients and the effect of condenser cooling water temperature on the evaporation process and the increase in freshwater condensate. The research methodology involved the analysis of heat and mass transfer in a solar desalination system. A desalination device was designed to test the evaporation process with seawater temperature heated using halogen lamp light. Results show that increasing seawater temperature from 27°C to 42°C results in condensation when the temperature reaches about 30°C, affecting the water surface pressure and evaporation rate. Evaporation and condensation efficiencies are affected by convection and evaporation heat transfer, resulting in a convection heat transfer (0.84296 W/m2. °C) and evaporation heat transfer coefficient (23.81353 W/m2.°C). This research demonstrates the potential of solar desalination technology in producing clean water.